The Mediating Role of Organizational Commitment between Job Satisfaction and Job Involvement on Teachers and Education Staffs’ - Mardalena, Mardalena; Basroh, Muhammad Ali; Arislan, Arislan; Sarinah, Sarinah (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2023)
Job performance is an important issue in an organization, including educational institutions. In this particular setting, this study was carried out to investigate the significance of job involvement and job engagement, facilitated by organizational commitment in elucidating job efficiency for teachers and staffs of SMA Negeri 2 Merangin. The population was 60 employees consisting of teachers and staffs. Total sampling was used since the population was under 100 people. Hypothesis development would be tested by Partial Least Square Structural Equation Modeling (PLS-SEM). The study results show that job satisfaction has a significant and positive effect on organizational commitment with bootstrap results of 0.367 with a t-count value of 3.274<t-table 1.96 with a P-value of 0.047>0.05. Furthermore, job involvement can influence organizational commitment significantly and positively with bootstrap results of 0.547 with a t-count value of 5.879>t-table 1.96 with a P-value of 0.000<0.05. Likewise, organizational commitment can influence job performance significantly and positively with bootstrap results of 0.279 with a t-count value of 2.052>t-table 1.96 with a P-value of 0.041<0.05. Then, organizational commitment can indirectly mediate job satisfaction which is 0.102 or 10.2%, and job involvement 0.179 or 17.9% toward job performance.